2019
DOI: 10.1002/jssc.201900134
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of a supercritical fluid chromatography tandem mass spectrometry method for the high‐throughput determination of nimodipine in beagle plasma

Abstract: A simple, sensitive, and efficient supercritical fluid chromatography with tandem mass spectrometry method was established for the determination of nimodipine in beagle plasma. One‐step protein precipitation with acetone was used to extract the analytes from the plasma. Nitrendipine was used as the internal standard. The chromatographic separation was achieved on an ACQUITY UPC2™ BEH 2‐EP column, and a gradient elution program was applied at a flow rate of 1.5 mL/min. The detection was carried out on a triple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…The developed method has LOD and LOQ of 0.014, 0.048 for AML, and 0.007,0.025 for NIM. Existing studies have shown LOD and LOQ greater than 0.2 and 0.5 for AML [ 11 , 12 ] and greater than 0.05 and 0.12 for NIM [ 13 , 14 ]. The new method demonstrated lower LOD and LOQ and, therefore, has higher sensitivity than published methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The developed method has LOD and LOQ of 0.014, 0.048 for AML, and 0.007,0.025 for NIM. Existing studies have shown LOD and LOQ greater than 0.2 and 0.5 for AML [ 11 , 12 ] and greater than 0.05 and 0.12 for NIM [ 13 , 14 ]. The new method demonstrated lower LOD and LOQ and, therefore, has higher sensitivity than published methods.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid chromatography-mass spectrometry (LC-MS) approaches are among the most widely applied strategies for the detection of a diverse range of compounds, and they are the primary strategy employed to analyze calcium antagonists in bio-samples including serum, plasma, and milk owing to their excellent sensitivity and acquisition speed [ 10 , 11 , 12 , 13 , 14 ]. The combination of high-performance liquid chromatography and ultraviolet detection (HPLC-UV) [ 11 ], gas chromatography-tandem mass spectrometry (GC-MS) [ 15 ], and GC with electron-capture detection (GC-ECD) have also been used in various research settings. However, LC-based strategies alone cannot provide sufficient sensitivity when detecting many compounds, given that samples containing complex substrates inevitably contain many spurious peaks for which effective separation cannot be achieved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The injector and detector were both 250°C, and the carrier gas was nitrogen (Xiang, Zhang et al 2014). To determine NIM in beagle plasma, a supercritical fluid chromatography tandem mass spectrometry technique was applied (Wang, Li et al 2019). A supercritical fluid chromatography-ESI-MS/MS technique had been developed to identify NIM and 3n-butylphthalide in the plasma of beagles.…”
Section: Chromatographic Methodsmentioning
confidence: 99%
“…Whereas ME in LC–MS has been extensively investigated and discussed (Matuszewski et al, 2003; Van Eeckhaut et al, 2009; Zhou et al, 2017), ME in SFC‐MS bioanalytical method development has not been systematically reviewed. As the use of SFC‐MS in the analysis of biological samples has increased, ME in SFC‐MS has also been investigated (Losacco et al, 2020; Wang, Li, et al, 2019) and reports have focused on the comparable analysis between the ME in SFC‐MS and other chromatographic techniques for achiral separation of biological samples (Svan et al, 2018; Wolrab et al, 2020).…”
Section: Introductionmentioning
confidence: 99%